Modulating Neuro-Endocrine Effects Of Bioactive Water Naftussya From Layers Truskavets' And Pomyarky At Humans With Dysfunction Of Neuro-Endocrine-Immune Complex - Igor L Popovych; Nadiya O Sydoruk; Anatoliy I Gozhenko; Walery Zukow (Kazimierz Wielki University, 2017)
Background. Previously we have been carry out comparative investigation long-term effects of Bioactive Water Naftussya from layers Truskavets', Pomyarky and Skhidnyts'a on some metabolic and biophysical parameters at men with dysfunction of neuro-endocrine-immune complex. The aim of this study is the investigation long-term effects on neuro-endocrine regulation at similar patients. Materials and methods. The object of observation were 20 volunteers: ten women and ten men aged 33-76 years without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism. We evaluated the trait and reactive anxiety, recorded EEG, HRV and blood pressure, determined levels of Cortisol, Aldosterone, Testosterone, Triiodothyronine and Calcitonin. After examination volunteers within 7 days used bioactive water Naftussya (250 mL three times a day) from Truskavets' or Pomyarky layer, then repeated the tests listed. Results. Weekly drinking of Bioactive Water Naftussya normalizes initially elevated levels of testosterone in women and reduces initially normal its level in men, in both sexes normalizes initially elevated levels of triiodothyronine and activity of the autonomic regulatory systems as the parasympathetic, so sympathetic, combined with a slight increase in the normal levels of aldosterone and trend to increase (under low) reactive anxiety as well as post occlusive reactivity of vascular tone. Among the 164 registered parameters quantitative EEG revealed noticeable changes only 8. This is, above all, normalizing increase initially reduced spectral power density (SPD) α-rhythm in loci T6 by 93%, P4 by 33%, F7 by 29%, increase by 10% in the normal range modal frequency of β-rhythm and further enhance SPD θ-rhythm in locus T5 by 42%. On the other hand, showed a reduction by 28% initially normal PSD of β-rhythm in locus in O2 and further reduction its by 20% in locus P4. Moreover, there was left-sided lateralization initially symmetric α-rhythm. No significant differences between the effects of Naftussya both deposits were found. Conclusion. Bioactive water Naftussya both Truskavets' and Pomyarky layers causes favorable normalizing effects on abnormalities neuro-endocrine parameters, which is a manifestation of its adaptogenic properties.